UPAYA MANAJEMEN SEKOLAH DALAM MENINGKATKAN MINAT ENTREPRENEURSHIP SISWA DI ERA DIGITAL: SEBUAH STUDI DI SMKN 1 LEMBAH MELINTANG, KABUPATEN PASAMAN, INDONESIA - Edi Supanri; Nizwardi Jalinus; Muhammad Anwar (Universitas Gara Nusantara Padangsidimpuan, 2025)
The rapid development of the digital era requires schools, particularly Vocational High Schools, not only to prepare graduates who are ready to enter the workforce but also to foster entrepreneurial interest and competencies to face dynamic business and industry challenges. However, the implementation of entrepreneurship education in schools still encounters several issues, such as limited resources, uneven utilization of digital technology, and the suboptimal role of school management in organizing entrepreneurship programs in a systematic manner. This study aims to analyze the efforts of school management in enhancing students’ entrepreneurial interest in the digital era based on the perceptions of teachers, school management, and students at SMKN 1 Lembah Melintang, Pasaman, Indonesia. This research employed a descriptive quantitative approach. The research subjects consisted of 42 teachers and school management members, as well as 145 students. Data were collected through online questionnaires distributed to all respondents. The collected data were analyzed using descriptive quantitative techniques by calculating frequencies and percentages for each research indicator. The results indicate that the majority of teachers, school management, and students are aware of the entrepreneurship programs implemented at the school. School management is perceived to have provided adequate support and encouraged the use of digital technology in entrepreneurship learning, although further optimization is needed, particularly in terms of practical entrepreneurial activities and supporting facilities. The entrepreneurship program was found to have a positive impact on increasing students’ entrepreneurial interest and contributed to the development of business-related skills relevant to the world of work. Nevertheless, the level of satisfaction, which was generally categorized as moderate, suggests the need to strengthen strategic planning, practice-based implementation, and collaboration with business and industry partners to ensure the sustainability and effectiveness of entrepreneurship programs in vocational schools..